2004
DOI: 10.1073/pnas.0401764101
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for vesicular glutamate transporter 1 (VGLUT1) in postnatal development and control of quantal size

Abstract: Quantal neurotransmitter release at excitatory synapses depends on glutamate import into synaptic vesicles by vesicular glutamate transporters (VGLUTs). Of the three known transporters, VGLUT1 and VGLUT2 are expressed prominently in the adult brain, but during the first two weeks of postnatal development, VGLUT2 expression predominates. Targeted deletion of VGLUT1 in mice causes lethality in the third postnatal week. Glutamatergic neurotransmission is drastically reduced in neurons from VGLUT1-deficient mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
447
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(494 citation statements)
references
References 44 publications
(74 reference statements)
33
447
1
8
Order By: Relevance
“…Increasing VGLUT1 increases quantal size and decreasing VGLUT1 or VGLUT2 decreases the amount of glutamate loaded into vesicles (Moechars et al, 2006; Fremeau et al, 2004;Wojcik et al, 2004). Fremeau et al (2004) suggested that there are different properties of release for VGLUT1 and VGLUT2 with more rapid recycling and recovery for VGLUT1.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing VGLUT1 increases quantal size and decreasing VGLUT1 or VGLUT2 decreases the amount of glutamate loaded into vesicles (Moechars et al, 2006; Fremeau et al, 2004;Wojcik et al, 2004). Fremeau et al (2004) suggested that there are different properties of release for VGLUT1 and VGLUT2 with more rapid recycling and recovery for VGLUT1.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult brain, VGluT1 predominates in the cerebral cortices and hippocampus, whereas VGluT2 expression is predominant in the diencephalon, brainstem, and spinal cord (Fremeau et al, 2001;Herzog et al, 2001;Wojcik et al, 2004). However, none of these brain regions exclusively expresses one isoform.…”
Section: Saturation Of Vglut1-and Vgat-immunopositive Synaptic Densitmentioning
confidence: 99%
“…At the experimental level, the vesicular glutamate transporter 1 (VGLUT1) has been reported to play a key role in the synaptic release (12) and the efficacy of glutamatergic synaptic transmission (13)(14)(15)(16). A recent study carried out in our laboratory reports that mice heterozygous for VGLUT1 (VGLUT1+/-), exhibit decreased cortical and hippocampal levels (35-45 %) of the inhibitory neurotransmitter GABA as well as helplessness in the forced swimming test (17).…”
Section: Introductionmentioning
confidence: 99%